Maltego Applied to the Colombian Contex (2018)
Who has social networks account?,2. Do you know what is public and what is private in yours accounts?,3. There is a lot of information about us on the web and on state platforms, so you have to be careful with your privacy.4. What are Open Sources?,1. Open sources of information are the places where all public information is located and does not have any type of access control